Use elimination to solve the system:

6x-4y=6

-6x+3y=0

6x-4y=6

-6x+3y=0

6x and -6x cancel each other out.

You are left with -1y=6

Therefore, y=-6

6x-4(-6)=6

6x+24=6

Subtract 24 from both sides.

6x=-18

Divide both sides by 6

X=-3

Final answers: x=-3 y=-6

6x+4y=6

-6x+3y=0

7y=6

y=6/7

use one of the equations above i picked the first one

6x+4y=6

6x+4(6/7)=6

6x+24/7=42/7

6x=18/7

x=3/7

6x-4y=6

-6x+3y=0supposed to be -y=6 y=-6 then 6x-4(-6)=6 6x+24=6 6x=-18 x=-3

it’s -4. I believe I was right.

RELATED: